Microstructure and Mechanical Properties of Rope Drum Casting - Futáš, Peter; Pribulová, Alena; Mahút, David; Bartosova, Marianna; Junáková, Andrea (Journal of Casting & Materials Engineering, 2018)
Ductile iron is a high-carbon-containing iron-based alloy in which the carbon, as graphite, is present in a spheroidal shape. With its good mechanical properties, ductile iron approximates the properties of steel and the cost per unit of strength compared to other materials. With suitable metallurgical treatments, we can influence its microstructure and resulting properties. Incorrect manufacturing technology and metallurgical processes give rise to casting defects and decreased mechanical properties. The contribution is devoted to measures to prevent the occurrence of defects in the casting of rope drums and to achieve the required mechanical properties of these castings. The most-common defects in these castings are micro-shrinkages in casting heat centers and unsatisfactory mechanical properties such as tensile strength, yield strength, and elongation.